HUMAN DUALISM OF ZAKI NAQUIB MAHMUD: Philosophical Arguments of Religious Moderation - Supriyanto Supriyanto (AL-TAHRIR, 2021)
Abstract: Human dualism is a debatable philosophical concept in various schools of philosophy. Through their leading thinkers, Greek philosophy, Western philosophy, and Islamic philosophy have contributed to the debate in the discourse of human dualism. Zaki Naquib Mahmud, an Egyptian rationalist philosopher, opposed the previous philosophers' dichotomous concept of human dualism. This article describes the conceptual correlation of Zaki Naquib Mahmud's dualism with religious moderation. Through a literature review of Zaki Naquib Mahmud's work, the results showed that (1) Zaki tended to reject the dichotomous thought of human dualism; (2) the implication of the rejection was the conceptual distinction between religion, being religious and religious knowledge; and (3) the inclusive awareness of the three concepts could extend a more moderate understanding in strengthening the concept of religious moderation philosophically.الملخص: مازالت الثنائية الفلسفية حول البشرية موضوع نقاش حار لدى المدارس الفلسفية المختلفة. قد ساهمت الفلسفة اليونانية والغربية والاسلامية على ايدي مفكريهم الرائدين اسهامات كبيرة في هذا البحث. قد عارض زكي نجيب محمود ، الفيلسوف العقلاني المصري ، مفهوم الثنائية البشرية الكلاسيكية من الفلاسفة القدماء. يجد هذا المقال العلاقة الفعالة بين ثنائية زكي نجيب محمود ومفهوم الوسطية الدينية. من خلال القراءة لاعمال زكي نجيب محمود نستنتج من هذه الدراسة ما يلي : (1) يميل زكي إلى رفض فكرة الثنائية المقسمة للازدواجية البشرية. (2) يؤدي هذا الرفض من زكي الى التفرقة بين مفهوم الدين والتدين والعلم الديني. (3) ويتولد من الوعي الصحيح بمعاني هذه الثلاثة الاعتدال والتوسط في إدراك المفاهيم الدينية، ويقوي فلسفيًا الوسطية الدينية الاسلامية.Abstrak: Dualisme manusia menjadi konsep filosofis yang terus menjadi bahan perdebatan dalam berbagai aliran filsafat. Filsafat Yunani, Filsafat Barat dan Filsafat Islam turut serta menyumbang perdebatan dan berkontribusi dalam diskursus dualisme manusia melalui para pemikir unggulannya. Zaki Naquib Mahmud, seorang filsuf rasionalis Mesir menentang konsep dualisme manusia yang dikotomis dari para filosof terdahulu. Artikel ini mendeskripsikan korelasi konseptual dualism manusia Zaki Naquib Mahmud dengan moderasi beragama. Melalui kajian kepustakaan terhadap karya Zaki Naquib Mahmud, hasil penelitian ini adalah (1) Zaki cenderung menolak pemikiran dualisme manusia yang dikotomis; (2) implikasi dari penolakan tersebut adalah pembedaan konseptual antara agama, beragama dan ilmu agama; dan (3) kesadaran terhadap pembedaan makna dari ketiga konsep tersebut dapat melahirkan pemahaman yang cenderung moderat karena adanya kesadaran inklusif sehingga memperkuat secara filosofis terkait dengan konsep moderasi beragama.